Analysis of Law No.6 /2023 Implementation on Resolving Industrial Relations Disputes in Courts - Husain, Ananda Dwi Nurvia (Universitas Negeri Gorontalo, 2024)
This article discusses the implementation of Law No. 6 of 2023 concerning Job Creation within the context of resolving industrial relations disputes in courts. Against the backdrop of the primary objectives of the Job Creation Law, which focus on enhancing investment and creating employment opportunities, this study analyzes how the new regulations affect the mechanisms for dispute resolution between workers and employers. The research methodology employed is a qualitative approach through literature review and interviews with legal practitioners, as well as the analysis of relevant court cases. The analysis results indicate that although the Job Creation Law aims to expedite the dispute resolution process, there are challenges in its implementation. These challenges include a lack of understanding among workers and employers regarding the new procedures and the potential for injustice arising from the reduction of workers' rights. The study also recommends the necessity of socialization and training for all related parties to improve understanding and acceptance of the regulatory changes, as well as the importance of supervision to ensure fairness in dispute resolution within the courts. Thus, this article contributes to a better understanding of the impact of the Job Creation Law on the dynamics of industrial relations in Indonesia